Banking on the Principles : Compliance with Basel Core Principles and Bank Soundness - Detragiache, Enrica; Demirguc-Kunt, Asli.; Tressel, Thierry (Washington, D.C. : International Monetary Fund, 2006)
This paper studies whether compliance with the Basel Core Principles for Effective Banking Supervision (BCPs) improves bank soundness. The authors find a significant and positive relationship between bank soundness (measured with Moody's financial strength ratings) and compliance with principles related to information provision2. Specifically, countries that require banks to regularly and accurately report their financial data to regulators and market participants have sounder banks. This relationship is robust to controlling for broad indexes of institutional quality, macroeconomic variables, sovereign ratings, and reverse causality. Measuring soundness through Z-scores yields similar results. These findings emphasize the importance of transparency in making supervisory processes effective and strengthening market discipline. Countries aiming to upgrade banking regulation and supervision should consider giving priority to information provision over other elements of the core principles.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet